Peningkatan Kemampuan Penalaran Matematis Siswa melalui Model Discovery Learning - Listika Burais; M. Ikhsan; M. Duskri (Didaktik Matematika, 2016)
The purpose of this study was to determine the differences between improvement of mathematical reasoning abilities of students who obtain a model of learning through discovery learning and students who received conventional teaching. This research was a quantitative study with experimental method, that has pretest-posttest group design. The population was all students at MTsN Lambalek by taking samples of two classes, namely class-VIIIA as the experimental class and VIIIB as the control class. Then, the data were collected by using testing techniques. The collected data were analyzed by ANOVA. Based on the results of the analysis, it can be concluded that the students' mathematical reasoning abilities in experimental class was better than the control class which was reviewed based on the whole student and grouping students.